Mission in Suffering Context - Harianto GP (Sekolah Tinggi Teologi Excelsius, 2019)
AbstractThis study aims to examine the mission in the context of suffering related to about theology of suffering, its context in Indonesia and its implications for mission in Indonesia. In connection with the goal, the results of the study show that suffering is the pressure faced by someone who comes from outside himself to exert a good influence on that person. The suffering of non-believers is different. If non-believers are suffering because of the world, but if believers suffer because of Christ. The suffering experienced by believers in Indonesia is indeed the Great Commission of Christ. Believers and the church are obliged to do God's mission is to win souls who are lost in their suffering by being a witness of God and dialogue to preach the gospel.Keywords: Mission; Suffer; Church; BelieversAbstractPenelitian ini bertujuan mengkaji mengenai misi dalam konteks penderitaan berkaitan dengan seputar teologi penderitaan, konteksnya di Indonesia dan implikasinya terhadap misi di Indonesia. Berkaitan dengan tujuan, hasil penelitian menunjukkan bahwa penderitaan ialah tekanan yang dihadapi seseorang yang datang dari luar dirinya untuk memberikan pengaruh yang baik kepada orang tersebut. Penderitaan orang yang bukan percaya dengan orang percaya berbeda. Kalau orang yang bukan percaya adalah penderitaan karena dunia tetapi kalau orang percaya menderita karena Kristus. Penderitaan yang dialami orang-orang percaya di Indonesia adalah memang amanat Agung Kristus. Orang percaya maupun gereja wajib melakukan misi Allah adalah memenangkan jiwa-jiwa yang tersesat dalam penderitaannya dengan cara adalah menjadi saksi Allah dan dialog untuk memberitakan Injil. Kata Kunci: Misi; Penderitaan; Gereja; Orang Percaya